A Study of the Efficacy of the Additional Administration of Tadalafil in Japanese Men with α1-Blocker-Resistant LUTS/BPH - Hayashi, Keiichiro; Fukagai, Takashi; Sasaki, Haruaki; Morita, Masashi; Igarashi, Atsushi; Koshikiya, Atsushi (Hinyokika kiyo. Acta urologica Japonica, 2016)
Alpha 1-blockers are widely used at present for lower urinary tract symptoms (LUTS)/benign prostatic hyperplasia (BPH). However, some patients experience little improvement of symptoms, and it is difficult to provide additional treatment. We have additionally administered tadalafil to patients with inadequate symptom improvement, despite treatment with alpha-1 blockers. The subjects were 57 patients with a diagnosis of LUTS/BPH who showed a poor response to treatment with alpha-1 blockers for 1 month or more (international prostate symptom score [IPSS] ≥8 and/or quality of life [QOL] index ≥3). Tadalafil 5 mg was administered on consecutive days to patients orally receiving alpha-1 blockers. We determined IPSS, the QOL index, overactive bladder symptom scores (OABSS), maximum urine flow, residual urine volume, and the sexual health inventory for men (SHIM) before, and 4, 8, and 12 weeks after administration, and then evaluated improvement effects. IPSS, the QOL index, OABSS, and SHIM showed significant improvement (P ＜0.05) at 4 weeks after the start of treatment and onward. IPSS and the QOL index showed greater improvement effects at 8 and 12 weeks. Residual urinary volume was significantly improved only at 8 weeks. However, the maximum urine flow showed no improvement at any time point. Our results demonstrated the additional administration of tadalafil to patients with LUTS showing poor responses to alpha-1 blockers to improve LUTS/BPH symptoms as well as sexual function.